Effects of a preconditioning oral nutritional supplement on pig livers after warm ischemia - Nickkholgh, Arash; Li, Zhanqing; Liang, Rui; Mikalauskas, Saulius; Groß-Weissmann, Marie-Luise; Zorn, Markus; Büchler, Markus W.; Schemmer, Peter (HPB surgery, 2012)
Several approaches have been proposed to pharmacologically ameliorate hepatic ischemia/reperfusion injury (IRI). This study was designed to evaluate the effects of a preconditioning oral nutritional supplement (pONS) containing glutamine, antioxidants, and green tea extract on hepatic warm IRI in pigs. Methods. pONS (70 g per serving, Fresenius Kabi, Germany) was dissolved in 250 mL tap water and given to pigs 24, 12, and 2 hrs before warm ischemia of the liver. A fourth dose was given 3 hrs after reperfusion. Controls were given the same amount of cellulose with the same volume of water. Two hours after the third dose of pONS, both the portal vein and the hepatic artery were clamped for 40 min. 0.5, 3, 6, and 8 hrs after reperfusion, heart rate (HR), mean arterial pressure (MAP), central venous pressure (CVP), portal venous flow (PVF), hepatic arterial flow (HAF), bile flow, and transaminases were measured. Liver tissue was taken 8 hrs after reperfusion for histology and immunohistochemistry.
Gesehen am 28.06.2018